Human Epidermal Growth Factor 2 (HER2) in Early Stage Uterine Serous Carcinoma: A Multi-Institutional Cohort Study - Erickson, Britt K. (Gynecol Oncol, 2020)
BACKGROUND: Human epidermal growth factor receptor 2 (HER2) has emerged as an important prognostic and therapeutic target in advanced stage and recurrent uterine serous carcinoma (USC). The significance of tumoral HER2 expression in early-stage disease has not been established. METHODS: This multi-center cohort study included women with stage I USC treated from 2000–2019. Demographic, treatment, recurrence, and survival data were collected. Immunohistochemistry (IHC) was performed for HER2 and scored 0–3+. Equivocal IHC results (2+) were further tested with fluorescence in-situ hybridization (FISH). HER2 positivity was defined as 3+ IHC or FISH positive. RESULTS: One hundred sixty-nine patients with stage I USC were tested for HER2; 26% were HER2-positive. There were no significant differences in age, race, stage, adjuvant therapy, or follow-up duration between the HER2-positive and negative cohorts. Presence of lymph-vascular space invasion was correlated with HER2-positive tumors (p=0.003). After a median follow-up of 50 months, there were 43 (25.4%) recurrences. There were significantly more recurrences in the HER2-positive cohort (50.0% vs 16.8%, p<0.001). HER2 positive tumors were associated with worse progression-free (PFS) and overall survival (OS) (p<0.001 and p=0.024). On multivariate analysis, HER2 positive tumors were associated with inferior PFS (aHR 3.50, 95%CI 1.84–6.67; p<0.001) and OS (aHR 2.00, 95%CI 1.04–3.88; p=0.039) compared to HER2-negative tumors. CONCLUSIONS: Given its significant association with worse recurrence and survival outcomes, HER2 positivity appears to be a prognostic biomarker in women with stage I uterine serous carcinoma. These data provide support for clinical trials with anti-HER2-directed therapy in early-stage disease.